THE PHENOMENON OF RELIGIOUS ACTIVITIES IN THE DIGITAL ERA: STUDIES ON INDONESIA STUDENTS - Muhamad Riza Chamadi; Kuntarto Kuntarto; Musmuallim Musmuallim; Muhamad Baedowi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
This study aims to describe the phenomenon of students carrying out religious activities in the digital era. This type of research is qualitative with a phenomenological approach. Data collection through questionnaires, documentation, and observation. The limitation of problems in classifying religious activities in question is in the form of Islamic da'wah activities that students participate in through social media platforms and student religious strengthening activities through gadget devices. Researchers conducted data analysis through respondent data classification, data reduction, and conclusion. This paper produces findings of two things, first, about students' religious activities in witnessing da'wah on social media, which dominantly chooses ustaz with melancholy content. Second, students in the digital era strengthen their religion more through electronic media than visiting teachers to read holy books, imitate worship procedures, and take religious literature that is considered relevant.